Desimination of Technology Application of Blood Flow Current Technology in Puskesmas - Iswanto Suwarno; Muhammad Ahmad Baballe; Irfan Ahmad; Erwin L. Rimban; Mohammad Aljanabi (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
Public health needs to be considered because it can create the ability to live healthy for every population which is the goal of health development which is part of human resource development. Muscle aches, muscle pain or spasms, and shoulder or joint stiffness are diseases that are often experienced by some people. To relieve the disease, people sometimes come to health development sites such as Puskesmas to do therapy. Some Puskesmas already have these therapeutic tools but there are some Puskesmas that do not have them because these tools are difficult to buy. This community service program is carried out by making infrared therapy devices which are then applied at the Kasih 1 Public Health Center. With this program, it is hoped that people can live healthy lives.